The Proceedings of the Third Workshop on Computer Modelling in Decision Making (CMDM 2018) 2019
DOI: 10.2991/cmdm-18.2019.3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Dynamics of Market Graph Characteristics

Abstract: In recent years the network models have been successfully employed for the analysis of the stock market. The network model of the stock market is defined as a full weighted graph, which vertices correspond to the returns of market assets, and the weights of the edges are determined by the measure of its interdependencies. To obtain important information from the network model, many researches extract subgraphs, which are called network structures. One of the most popular network structures is the so called mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Indeed, graphs, mathematical models of networks, have been shown to be useful tools to model complex relationships between assets. Early work by Mantegna [26][27][28] analyze stock markets using graphs built using Pearson, Spearman rank and Kendall correlation, respectively. Millington and Niranjan's (2021) [29] work compares networks built using these different correlations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Indeed, graphs, mathematical models of networks, have been shown to be useful tools to model complex relationships between assets. Early work by Mantegna [26][27][28] analyze stock markets using graphs built using Pearson, Spearman rank and Kendall correlation, respectively. Millington and Niranjan's (2021) [29] work compares networks built using these different correlations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The market graph constructed with use of the measure linearly dependent on the sign correlation was studied in [23,32]. The paper showed that the measure is capable for the analysis of the market graphs.…”
Section: Market Network Constructionmentioning
confidence: 99%
“…In accordance with the efficient market hypothesis, it is assumed that stock prices of companies and their mutual behavior reflect all publicly available information about companies. Thus, economic and financial connections between companies may be reflected by the correlation of the log returns of company assets [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. • Some researchers believed that a connection between companies arises, if both companies have common members of the board of directors [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%